Charting A Sustainable Path: Analyzing GRI-Compliant Reporting in Indonesia's Healthcare Sector (Public Accounting and Sustainability, 2025)
Research aims: This research seeks to analyze the sustainability reporting practices of private hospital companies in Indonesia, with a particular focus on a prominent hospital group, to evaluate their compliance with the Global Reporting Initiative (GRI) Standards and identify opportunities for enhancement. Design/Methodology/Approach: The study employs a qualitative methodology, utilizing content analysis to examine the provider's 2023 Sustainability Report thoroughly. The assessment is conducted under the GRI standards, a widely recognized framework for sustainability reporting. This comprehensive evaluation encompasses various aspects, including general disclosures, economic performance, environmental management, and social and governance dimensions. Research findings: The healthcare group has broadly followed the GRI guidelines, especially in general disclosures, economic performance, and environmental management. However, there are still gaps in fully addressing social and governance aspects, indicating opportunities for improvement. Theoretical contribution/Originality: This research contributes to the theoretical understanding of sustainability reporting in the healthcare sector by exploring its application within a private hospital context in Indonesia. It enriches the literature on sustainability practices in non-traditional industries such as healthcare. Practitioner/Policy implication: This study provides practical recommendations for improving the transparency and compliance of sustainability reporting within healthcare organizations. Policymakers and regulators can use these insights to harmonize sustainability reporting standards across the sector and enhance the accountability of healthcare providers. Research limitation/Implication: The study is exclusively centered on a specific private hospital group, restricting its applicability to other healthcare organizations or private hospital companies. Future research could examine sustainability reporting practices across a broader spectrum of domestic and international healthcare providers.